Reconstruction of Election Observer to Build Institutional Partnerships with Election Organizers in Indonesia - Fauzani, Muhammad Addi; Hakiki, Yuniar Riza (Law Research Review Quarterly, 2018)
Republic of Indonesia Election Supervisory Body (Bawaslu) Regulation Number 4 of 2018 concerning Election Monitoring (Election) regulates Election Oversight to support the role of Bawaslu as the Election organizer who supervises the implementation of elections. However, in its implementation the position of Election Observers still tends to be ambiguous, so that its role has not been running optimally. Therefore, the regulation regarding Election Monitoring needs to be reconstructed to support the realization of the implementation of General Elections in accordance with the principles and regulations. This study examines 2 (two) problem formulations, first, what is the urgency of the Election Observation reconstruction ?; secondly, how is the concept of the Election Monitoring reconstruction to build an institutional partnership with the Election organizers in Indonesia ?. This research is a normative legal research with a conceptual approach. The study concludes, first, that Election Oversight needs to be reconstructed because its institutional relationship with Bawaslu is very ambiguous, so that its monitoring role is potentially ineffective; arrangements that have not yet reached the description of the task of the Election Oversight to take part in the prevention and enforcement of violations; and the low interest of the community in participating in Election Monitoring. Second, as a step to build an institutional partnership with the election organizers, the structure and institutional relations of the Election Monitoring need to be reorganized; arranged and clarified job descriptions; as well as the state needs to allocate operational funds for accredited Election Observers.